Oral submucous fibrosis presenting with histopathological lichenoid changes as predominant feature: Report of five cases and review of the literature. (1st July 2021) - Campos, María C.; Tubau, Carla; Segura, Sonia; González‐Farré, Monica; Iglesias‐Sancho, Maribel; Fernández‐Figueras, María Teresa; Garcia‐Muret, Maria Pilar; Mozos, Ana
Abstract: Oral submucous fibrosis (OSF) is a precancerous condition of the oral cavity associated with habitual chewing of quid, with a high incidence among populations of the Indian subcontinent and Southeast Asia. Clinically, its initial manifestation may mimic oral lichen planus or lichen sclerosus. If the habit is not halted, the mucosa gets leathery and thickened, and fibrous bands form causing significant morbidity. Microscopically, it is characterized by atrophic epithelium, loss of rete ridges, and hyalinization of lamina propria. Of note, these hallmark histopathological features may be overlooked in the unusual presence of lichenoid interface changes, which may lead to the wrong diagnosis. We present herein five cases in which the rare joint appearance of OSF and lichenoid reaction features posed a diagnostic challenge. Due to its progressive nature and malignant potential, the presence of oral lichenoid changes overlying submucous hyalinization, in the right clinical and demographic setting, should raise suspicion of OSF and prompt actions directed at quid‐chewing discontinuation.